Effects of soil types and fertilizers on growth performance of RevoTropix Paulownia - James Gerusu, Geoffery; Ismail, Nur Bazilah; Mohamed Zulperi, Dzarifah; Karam Singh, Daljit Singh; Sundara Rajoo, Keeren (The Malaysian Society of Soil Science (MSSS), 2024)
RevoTropix Paulownia (RT-Paulownia), a fast-growing species known for its adaptability, was evaluated for growth performance on different soil types with varying fertilizer treatments. This study examines the growth and survival of RT-Paulownia saplings across three forest reserves in Sarawak: Sabal Forest Reserve (Ultisols), Sampadi Forest Reserve (Ultisols), and Sarawak Mangrove Forest Reserve (Spodosols). A randomized complete block design assessed three treatments: Control (no fertilizer), chemical fertilizer, and organic fertilizer. A total of 231 trees were planted at each site, and data were collected over 20 months. Results showed that soil type and fertilizer significantly affected tree performance. Chemical fertilizer consistently improved survival and growth, with Sabal FR (Ultisols) showing the best performance. Trees treated with chemical fertilizer reached an average diameter at breast height (DBH) of 8.96 cm and a height of 763.68 cm. Conversely, untreated trees in Sampadi FR (Ultisols) experienced total mortality within 10 months, though organic fertilizer promoted better growth for surviving trees. Spodosols presented the most challenging conditions, with low survival rates across all treatments, though chemical fertilizer again yielded the highest performance. This study highlights the importance of soil type and targeted nutrient management in optimizing RT- Paulownia plantation success. Further research is recommended to explore long-term growth patterns and potential fertilizer strategies.